Complicated Relationship between Genetic Mutations and Phenotypic Characteristics in Transient and Permanent Congenital Hypothyroidism: Analysis of Pooled Literature Data - Wei Long; Lingna Zhou; Ying Wang; Jiaxuan Liu; Huaiyan Wang; Bin Yu (International Journal of Endocrinology)
Purpose. Mutations and phenotypic characteristics remain unclear in patients with congenital hypothyroidism (CH), and no study concerning whether the outcome of transient CH (TCH) or permanent CH (PCH) is determined by mutations has been reported. Methods. We searched the literature up to April 2019. Eligible studies and data extraction were performed. We estimated the relationship between mutations and phenotypic characteristics in pooled patients with CH. Results. Two hundred forty-one cases were pooled from 41 eligible studies. The thyroid morphology, classification of mutated genes, and types of mutations were different between 94 patients with TCH and 147 patients with PCH. Heterozygous missense mutations prevailed in PAX8, TSHR, FOXE1, and NKX2-5, and patients with these mutated genes had a higher risk of PCH (OR = 37.38, 95% CI 5.04–277.21, P<0.001). TCH and PCH have equal shares in patients with mutated DUOX2 or DUOXA2. Dual-site and multisite mutations were frequently detected in DUOX2. High phenotypic heterogeneity was observed in mutated DUOX2 even in the same mutations. However, there was no relationship found between mutations and transient or permanent outcome in patients with mutated DUOX2. Conclusion. Transient or permanent outcomes were influenced by the biological function of mutated genes instead of types of mutations among patients with CH. Patients whose mutations were related to thyroid dysgenesis (TD) were more likely to have PCH. The relationship between mutations and phenotypic characteristics is complicated, and phenotypic characteristics may be affected by mutations and other factors.